Adolescent Gender and Age Differences in Responsiveness to Functional Family Therapy. Issue 4 (22nd November 2019) - Scavenius, Christoffer; Granski, Megan; Lindberg, Malene Rudolf; Vardanian, Maria Michelle; Chacko, Anil
Abstract : The current study contributes to a sparse literature on moderators of Functional Family Therapy (FFT) by examining whether responsiveness to FFT, measured by a broad range of outcomes, varies by adolescent gender, age, and their interaction. This study was informed by 687 families ( n, adolescents = 581; n, caregivers = 933) and utilized a pre–post comparison design. Fixed‐effects regressions with gender, age, and their interaction included as explanatory variables were conducted to calculate the average change in youth mental health, callous–unemotional traits, academic outcomes, substance use, and family functioning. Moderation analyses revealed that according to parent report, girls had significantly greater improvements in peer problems and family functioning, and boys benefited more in increased liking of school. There were differential effects by age, such that older youth had less beneficial mental health outcomes and a smaller decrease in frequency of hash use. The gender by age interaction was significant for adolescents' report of mental health and family functioning outcomes, which suggests that girls benefit from FFT less than boys during early adolescence, but benefit more than boys in late adolescence. This finding adds to literature which has evidenced that family functioning is particularly important for girls by suggesting that FFT is important for improving older girls' mental health and family functioning in particular. The study's results expand the examination of outcomes of FFT to include academic outcomes, and provide insight into key factors that should be considered in addressing adolescent behavioral problems and family functioning. Abstract : El presente estudio contribuye a una bibliografía escasa sobre los moderadores de la terapia familiar funcional (TFF) analizando si la capacidad de respuesta a la TFF, medida por una amplia gama de parámetros, varía según el género, la edad y la interacción de los adolescentes. Este estudio se valió de 687 familias ( n, adolescentes=581; n, cuidadores= 933) y utilizó un diseño de comparación previa y posterior. Se llevaron a cabo regresiones de efecto fijo con el género, la edad y su interacción incluidos como variables explicativas a fin de calcular el cambio promedio en la salud mental, los rasgos de insensibilidad emocional, los resultados académicos, el consumo de sustancias y el funcionamiento familiar de los jóvenes. Los análisis de moderación revelaron que de acuerdo con el informe de los padres, las niñas tuvieron mejoras considerablemente mayores en los problemas con los pares y el funcionamiento familiar, y los niños se beneficiaron más en el mayor agrado de la escuela. Hubo efectos diferenciales según la edad, de modo que los jóvenes de más edad tuvieron menos resultados beneficiosos en la salud mental y una disminución más pequeña en la frecuencia del consumo de hachís. La interacción del género según la edad fue significativa para los resultados del informe de salud mental y funcionamiento familiar de los adolescentes, que sugiere que las niñas se benefician de la TFF menos que los niños durante la adolescencia temprana, pero se benefician más que los niños en la adolescencia tardía. Este hallazgo aporta a la bibliografía que indica que el funcionamiento familiar es particularmente importante para las niñas, sugiriendo que la TFF es importante para mejorar la salud mental y el funcionamiento familiar de las niñas de más edad en particular. Los resultados del estudio amplían el análisis de los resultados de la TFF para incluir los resultados académicos, y permiten conocer mejor los factores clave que deben tenerse en cuenta a la hora de abordar los problemas conductuales y el funcionamiento familiar de los adolescentes. Abstract : 已有的关于功能性家庭疗法（FFT）的调和因素的研究还非常少，本研究将在此方面作出一些贡献，它旨在考察由各种结果测量而得的对FFT的反应性是否随青少年性别，年龄，和这些因素的相互作用而发生变化。这项研究参与对象有687个家庭（ n ，青少年= 581； n ，照顾者= 933），并采用了实验前和实验后的比较设计。调节分析的结果显示，根据父母的报告，女孩在同伴问题和家庭功能方面的进步明显更大，而男孩在增加对学校的喜爱程度方面受益更多。按年龄看影响有不同程度，对年龄较大的年轻人而言，有益的心理健康结果较少，散列使用频率的减少幅度较小。按年龄进行的性别分析对于青少年自己报告的关于心理健康和家庭功能结果具有重要意义。在青少年早期，女孩从FFT中获利少于男孩，而在青少年后期，女孩则比男孩从中受益更多。这一发现贡献了新的文献，此研究结果表明了FFT对于改善年龄稍大一点女孩的心理健康和家庭功能尤其重要，从而证明了家庭功能对女孩特别重要。这项研究的结果扩大了对FFT结果的考察范围，使其涵盖了学术成绩，并提供了解决青少年行为问题和家庭功能时应考虑的关键因素的见解。